2019
DOI: 10.1119/1.5085437
|View full text |Cite
|
Sign up to set email alerts
|

Manual timing in physics experiments: Error and uncertainty

Abstract: Manual digital timing devices such as stopwatches are ubiquitous in the education sector for experimental work where automated electronic timing is unavailable or impractical. The disadvantage of manual timing is that the experimenter introduces an additional systematic error and random uncertainty to a measurement that hitherto could only be approximated and which masks useful information on uncertainty due to variations in the physical conditions of the experiment. A model for the reaction time of a timekeep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Due to the need for precise measurement and the inherent margin of error with manual timing the ST must be recorded using a video camera capable of at least 30 frames per second (accurate to 0.033 s) and preferably 60 frames per second (accurate to 0.017 s) ( 54 ). The camera should be positioned in line with the finish line and out of the way of the dog's path.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the need for precise measurement and the inherent margin of error with manual timing the ST must be recorded using a video camera capable of at least 30 frames per second (accurate to 0.033 s) and preferably 60 frames per second (accurate to 0.017 s) ( 54 ). The camera should be positioned in line with the finish line and out of the way of the dog's path.…”
Section: Methodsmentioning
confidence: 99%
“…In 2019, we estimated the characteristic human reaction time for a manually-operated timing device from 4304 swimming competition race times obtained where races were started electronically and finished both electronically and manually. 37 We found that the reaction time for a single manual time measurement was modeled by a normal distribution with a mean of 0.…”
Section: B Timing Devicesmentioning
confidence: 97%
“…A difference of 0.1 s is of similar order to the expected variation of human reaction time for a stopwatch. 37 The presentation of the incorrect display digit is not a property of the particular algorithm used here. Any truncation algorithm would have the same issues of rounding.…”
Section: B Timing Devicesmentioning
confidence: 99%
“…As a proof of concept distinct from prior works, we conduct investigations on learning from noisy independent variables, e.g. polluted spatial and temporal variables, which are relevant to Global Positioning System (GPS) coordinate measurements [20] and manual timing in physical experiments [21].…”
Section: Introductionmentioning
confidence: 99%